Faktor Penentu Ketahanan Ekonomi UMKM Jakarta dalam Menembus Pasar Global - Allo, Elisabeth; Prijadi, Ruslan; Chatib, Chotib (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2024)
This study aims to analyze the factors that make MSMEs have economic resilience so that they can enter the global market/go international. The approach used is qualitative research, using in-depth interview techniques with 3 representatives of MSME actors from Jakarta Entrepreneur who have successfully entered the international market. Data in the form of narratives/in-depth interview texts were processed using Dedoose software. The results of the study indicate that there are supporting factors for MSMEs to be able to penetrate the international market which also support their economic resilience, namely: collaboration, training, registration, marketing, financial reporting, coaching experience, enjoying the journey of ups and downs with various joys and sorrows of becoming an entrepreneur, broad insight, and the process of learning and transferring knowledge.